A defesa dos direitos dos migrantes pelo Comitê Estadual Intersetorial de Atenção aos Refugiados, Apátridas e Migrantes do Rio Grande do Norte: os desafios para o cumprimento do direito internacional - Rocha, Isly Queiroz Maia (2021)
Facing the intensification of the influx of people between borders and the advancement of cooperated solutions to the migration phenomena, the subnational bodies have been increasingly involved in the migratory governance. The rapprochement of this area of interest considers the obligations inherited by the national public bodies, before the responsibilities taken over by the States internationally. The current investigation was developed envisaging the observation of measures adopted by the State of Rio Grande do Norte, through the recent Intersectoral State Committee on the Attention to Refugees, Stateless Persons and Migrants of Rio Grande do Norte (CERAM/RN), in relation with the international standards for migrant’s rights protection. Regarding the reserved powers assigned to the member-states by art. 25, § 1º, of the Federal Constitution, the question is to define the rights whose assurance remains within the limits of the federated state’s responsibility and then verify in what measure the normative activity of CERAM/RN responds to international law. To this end, the method of research employed was exploratory, adopting the procedures of documental and bibliographical analysis and direct observation. From this observation, it was verified that the member-states can be demanded to fulfill a broad body of international norms that assign the migrants subjective rights. Thus, the states meet an intermediary position, steered by the federal laws, from which they owe obedience, and limited by the municipality’s power to refer to local interests, making the cooperative federalism an adequate means chosen by the Brazilian State to ensure migrants’ rights. The concurrent examination of the international law in force in Brazil and the experience from CERAM/RN showed that the committee’s capacity to act is limited, although it functions as an articulator and promotor of migrants’ rights in accordance with international law standards. In that way, it has no competence to act on the implementation of those rights, such responsibility remains in the field of the active bodies of the Administration, as well as the Judiciary in it’s role safeguarding the law.